Literature Review: The Effect of Corporate Governance and its Impact on Sustainability Performance - Nabila Yolanda; Silitongga, Juliarta Elisabeth; Izzati, Dina; Maisyarah, Renny (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This literature review explores the relationship between corporate governance and business sustainability, emphasizing how effective governance practices enhance transparency and accountability. In today’s competitive landscape, companies strive to increase their value to ensure long-term survival and growth. Good Corporate Governance (GCG) is pivotal in achieving these goals, particularly considering past financial scandals that highlighted governance failures. Key principles such as fairness, responsibility, transparency, and accountability are discussed in relation to their impact on stakeholder trust and decision-making. The review also examines the interplay between corporate governance and Corporate Social Responsibility (CSR), demonstrating how both approaches contribute to a positive corporate image and stakeholder engagement. Through qualitative analysis of recent research, the review identifies critical factors influencing corporate performance, including board composition and institutional ownership. Findings suggest that companies prioritizing good governance not only enhance financial performance but also promote social and environmental responsibility. This underscores the importance of adopting comprehensive governance frameworks as a strategic approach to achieving sustainable competitive advantage and ensuring long-term business success. Ultimately, this review highlights the necessity for organizations to integrate governance and sustainability practices to foster resilience in an ever-evolving market.